Angiographic Analysis of Trans-Radial Percutaneous Coronary Intervention Cases by the Backup Support of Guide Extension Catheter (Bangladesh Heart Journal, 2018)
Background:The guide extension catheter – Guidezilla (Boston Scientific, United States of America) is a useful adjunctive tool in percutaneous revascularization of complex coronary lesions, and provides an extension to the guide catheter with better coaxial alignment, support and stability.Objective: The objective of this study was to describe the usefulness and easy deliverability of stent by Guidezillain the trans-radial treatment of complex coronary lesions as our initial experience.Methods:This prospective observational study was conducted at the Department of Cardiology, Ibrahim Cardiac Hospital & Research Institute (ICHRI), Dhaka from July 2016 to September 2017. The transradial approach was used in all cases. Clinical, angiographic and procedural data of percutaneous coronary interventions performed using Guidezilla, including indications for use of Guidezilla were collected and analyzed.Results:A total of 19 procedures (in 18 patients) were evaluated. 57.89% of cases were related to left circumflex coronary artery or obtuse marginal branch. The commonest challenge for use of Guidezillawas proximal angulation (63.15%) and calcification (47.4%). Commonest type of lesion was ACC/ AHA Type C lesion (63.2%). Successful stent deployment was achieved in 16 of the 19 procedures (84.2%). Among the unsuccessful cases, there was stent damage in one case and distal dissection after deployment of a stent in other. Stent deployment was not possible in two cases, due to diffuse lesion and heavy calcification.Conclusions:Guide extension catheter is a good trans-radial back-up support for calcified, complex and tortuous coronary anatomy, which otherwise may have been considered unsuitable for PCI. The use of such support can reduce the necessity for the more expensive alternative of deploying multiple small stents in order to traverse the lesions.Bangladesh Heart Journal 2018; 33(1) : 54-60